SINEMATOGRAFI DALAM PENYAMPAIAN EMOSI NON-VERBAL PADA FILM TAK KEMBALI LAGI - I Gusti Agung Deta Nanda Nugraha; I Made Denny Chrisna Putra; I Wayan Agus Mahardika (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2026)
The short film Tak Kembali Lagi is a fictional drama-romance work that explores the dynamics of a relationship breakdown through a non-verbal emotional approach. This work is based on the idea that conflicts in relationships do not always emerge through explicit verbal confrontation, but rather develop gradually through silence, emotional distance, and routines that lose their meaning. Therefore, cinematography is positioned as the primary visual language in conveying the characters’ inner states and relational dynamics. This article examines the creative process of Tak Kembali Lagi with a focus on the role of the Director of Photography (DOP) in designing and implementing visual aesthetics that support emotional storytelling. A realist approach is employed as the aesthetic foundation through the application of cinematographic techniques such as long takes, natural lighting, negative space composition, and frame-in-frame. The creation method consists of concept exploration, pre-production, production, and post-production stages. The results indicate that cinematography plays a significant role in communicating non-verbal emotions and enhancing the audience’s emotional experience without reliance on dialogue.